Variation in key leaf photosynthetic traits across wheat wild relatives is accession dependent not species dependent. Issue 6 (10th September 2020) - McAusland, Lorna; Vialet‐Chabrand, Silvere; Jauregui, Iván; Burridge, Amanda; Hubbart‐Edwards, Stella; Fryer, Michael J.; King, Ian P.; King, Julie; Pyke, Kevin; Edwards, Keith J.; Carmo‐Silva, Elizabete; Lawson, Tracy; et al.
Summary: The wild relatives of modern wheat represent an underutilized source of genetic and phenotypic diversity and are of interest in breeding owing to their wide adaptation to diverse environments. Leaf photosynthetic traits underpin the rate of production of biomass and yield and have not been systematically explored in the wheat relatives. This paper identifies and quantifies the phenotypic variation in photosynthetic, stomatal, and morphological traits in up to 88 wheat wild relative accessions across five genera. Both steady‐state measurements and dynamic responses to step changes in light intensity are assessed. A 2.3‐fold variation for flag leaf light and CO2 ‐saturated rates of photosynthesis A max was observed. Many accessions showing higher and more variable A max, maximum rates of carboxylation, electron transport, and Rubisco activity when compared with modern genotypes. Variation in dynamic traits was also significant; with distinct genus‐specific trends in rates of induction of nonphotochemical quenching and rate of stomatal opening. We conclude that utilization of wild relatives for improvement of photosynthesis is supported by the existence of a high degree of natural variation in key traits and should consider not only genus‐level properties but variation between individual accessions.